The religious experience in Søren Kierkegaard’s philosophy: The nature of the knight of faith - Espericueta, José Luis (Pensamiento. Revista de Investigación e Información Filosófica, 2022)
The purpose of this work is to distinguish the phenomenon of religious experience in the context of the philosophy of Søren Kierkegaard. The structure of Kierkegaardian thought will be reviewed and its theoretical framework will be analyzed to indicate how it makes religious experience a highly disturbing phenomenon for that person who lives it. It will be observed that this phenomenon, under the theoretical coordinates of Danish, becomes an extremely problematic event insofar as it is necessarily opposed to what is considered aesthetic and ethical. Religious experience is conceived here not as a passively received experience, but as a heartbreakingly demanding and anguished interpellation that demands action.
Keywords: religious experience; Kierkegaard; philosophy of religion